2019
DOI: 10.1177/1534735419828823
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Postural Control and Altered Sensory Organization During Quiet Stance Following Neurotoxic Chemotherapy: A Preliminary Study

Abstract: Individuals diagnosed with chemotherapy-induced peripheral neuropathy (CIPN) demonstrate impaired balance and carry an increased risk of falling. However, prior investigations of postural instability have only compared these individuals against healthy controls, limiting the understanding of impairments associated with CIPN. Therefore, the purpose of this study was to better isolate postural control impairments that are associated with CIPN. Twenty cancer survivors previously diagnosed with breast or colorecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 29 publications
(71 reference statements)
2
42
1
Order By: Relevance
“…People with PN demonstrate increased sway with their eyes closed and more sway response to visual flow. 10,11 Decreased use of an ankle strategy is also noted as is decreased reaction time which both can increase the risk of falling 12 .…”
Section: Background and Purposementioning
confidence: 99%
“…People with PN demonstrate increased sway with their eyes closed and more sway response to visual flow. 10,11 Decreased use of an ankle strategy is also noted as is decreased reaction time which both can increase the risk of falling 12 .…”
Section: Background and Purposementioning
confidence: 99%
“…Sway amplitude, including the root mean square (RMS) of the resultant sway [ 30 ], the mediolateral (ML) sway [ 25 , 29 ], and the total sway area [ 25 , 26 , 28 ] were greater in cancer survivors than healthy controls. Sway velocity, including the mean velocity of ML sway [ 25 , 28 ] and mean velocity of the resultant sway [ 24 ] were also greater in cancer survivors than that in controls. Three studies (the majority of participants had breast cancer) [ 31 33 ] assessed the longitudinal effect of chemotherapy on spontaneous sway and found that sway amplitude (area, ML RMS, AP RMS) and sway velocity (AP mean velocity, ML mean velocity) parameters worsen after treatment.…”
Section: Resultsmentioning
confidence: 99%
“…taxanes. Patients display deficits in the spatiotemporal parameters (speed and stride) of walking gait, in control of posture, and in balance relying on proprioception 49,50 . Acknowledging that these disabilities may arise from a variety of lesions in the nervous system, the deficits we observe here in the initial detection and encoding of muscle mechanics would necessarily impair movements and postures and cannot be fully compensated by other senses, e.g.…”
Section: Discussionmentioning
confidence: 99%